Effect of Early Bathing on Temperature of Normal Newborn Infants - P Alizadeh Taheri; H Fakhraee; K Sotoudeh (Tehran University of Medical Sciences, 2007)
Background: Nowadays there is a strong tendency for early bathing of healthy newborns but little is known about the ther¬mal stability of newborns in response to early bathing. The aim of this study was to compare the thermal effect of bathing on healthy newborn within 1-2 h of life versus 4-6 h after birth. Methods: In this randomized comparative study 100 healthy newborns in a newborn nursery of a charity hospital in Tehran were studied. The inclusion criteria were: healthy term (≥ 37 wk) newborn over 2500 grams with rectal temperature > 36.5 °C , apgar score > 7 in 1 and 5 min after birth and lack of manifestations of any diseases like sepsis or respiratory distress syn¬drome .The exclusion criteria were the history of recent fever, leukocytosis , urinary tract infections and using medi¬cines in their mothers. In the experimental group, 50 newborns were bathed within the first 1-2 h of birth; those in control group were bathed at the 4-6 h of age. Rectal temperatures were measured in four different times: before bathing and immedi¬ately as well as 30 and 60 min after bathing. Results: Rectal temperatures as measured at four different times did not differ significantly between infants bathed within 1-2 h of birth and those bathed 4-6 h after birth .There were no significant differences between the groups in types of gen¬der, birth weight, gestational age, parity, delivery route, interval time between rupture of membranes and delivery, apgar scores at 1 and 5 min of age. Conclusions: Healthy full term newborns with rectal temperature > 36.5 °C can be bathed within 1-2 h of birth without any risk of hypothermia.